Situation Report: Poland, 26 October 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Polish and Soviet Leaders Meet Wankowicz Trial Starts Mongolian Delegation in Warsaw Polish Trade Delegation to Visit Belgium and Luxemburg Soviet Broadcast on Monolithic Unity